2024
DOI: 10.1002/dev.22456
|View full text |Cite
|
Sign up to set email alerts
|

Quality not quantity: Deficient juvenile play experiences lead to altered medial prefrontal cortex neurons and sociocognitive skill deficits

Jackson R. Ham,
Madeline Szabo,
Jessica Annor‐Bediako
et al.

Abstract: Reduced play experience over the juvenile period leads to adults with impoverished social skills and to anatomical and physiological aberrations of the neurons found in the medial prefrontal cortex (mPFC). Even rearing rats from high‐playing strains with low‐playing strains show these developmental consequences. In the present study, we evaluated whether low‐playing rats benefit from being reared with higher playing peers. To test this, we reared male Fischer 344 rats (F344), typically thought to be a low‐play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 117 publications
0
0
0
Order By: Relevance
“…Critically, observations of rats have revealed that role reversals are among the critical experiences derived from play fighting that leads to improvements in sociocognitive skills (Pellis et al, 2023a). As noted above, a key feature of play fighting is that it involves cooperation, which in turn, is necessary to produce role reversals (turn-taking), and the studies with rats increasingly point to these beneficial effects arising from partners being relatively balanced in instigating role reversals (Stark et al, 2021;Ham et al, 2024). Not surprisingly, then, in Belding's ground squirrels, it is social play and not solitary locomotor play that is positively correlated with improved emotional responsivity and social competence (Marks et al, 2017).…”
Section: The Adaptive Functions Of Play Fightingmentioning
confidence: 99%
“…Critically, observations of rats have revealed that role reversals are among the critical experiences derived from play fighting that leads to improvements in sociocognitive skills (Pellis et al, 2023a). As noted above, a key feature of play fighting is that it involves cooperation, which in turn, is necessary to produce role reversals (turn-taking), and the studies with rats increasingly point to these beneficial effects arising from partners being relatively balanced in instigating role reversals (Stark et al, 2021;Ham et al, 2024). Not surprisingly, then, in Belding's ground squirrels, it is social play and not solitary locomotor play that is positively correlated with improved emotional responsivity and social competence (Marks et al, 2017).…”
Section: The Adaptive Functions Of Play Fightingmentioning
confidence: 99%